Saccharomyces cerevisiae boulardii CNCM I-1079 supplementation in finishing male pigs helps to cope with heat stress through feeding behaviour and gut microbiota modulation. Issue 3 (14th February 2022) - Labussière, Etienne; Achard, Caroline; Dubois, Serge; Combes, Sylvie; Castex, Mathieu; Renaudeau, David
Abstract: Pigs subjected to heat stress (HS) decrease their feed intake and growth. The objectives of the experiment were to determine the effects of live yeast (LY) supplementation ( Saccharomyces cerevisiae var boulardii CNCM I-1079) on feeding behaviour, energy metabolism and faecal microbiota composition of finishing boars ( n 10) housed in a respiration chamber at thermoneutrality (7 d at 22°C) or during HS (seven plus six days at 28°C). Dietary LY supplementation increased DM intake ( P = 0·01) whatever the ambient temperature, whereas HS decreased feed intake whatever the dietary supplementation ( P = 0·01). Dietary LY supplementation increased the number of meals ( P = 0·02). Energy retention was higher with dietary LY supplementation ( P < 0·01) but decreased during HS ( P < 0·01). The skin temperature of the supplemented pigs was lower at thermoneutrality and increased during HS to a lesser extent than that of non-supplemented pigs ( P < 0·01). Faecal microbiota composition was determined using 16S rRNA gene sequencing. Treponema, Christensenellaceae R-7, Ruminococcaceae UCG-002, Rikenellaceae RC9, Clostridium sensu stricto 1 and Romboutsia genera and some bacteria belonging to Alloprevotella, Oxalobacter and Anaeroplasma genera were more abundant under HS. LY supplementation attenuated HS effects on Romboutsia abundance, while decreasing the abundance of some bacteria from Ruminoccocus, Coprococcus, Peptococcus and Oxalobacter genera and increasing the abundance of beneficial bacteria from Lactococcus and Subdoligranulum genera. Our results suggest that higher level of the keystone species Ruminococcus bromii at thermoneutrality may be one of the causes for higher energy retention observed under subsequent HS.